The Role of Waste Bank Management Information System in Increasing Community Participation in Environmental Management in Dumai City - Ramadhani, Suci; Anggasta, Giovany; Nazira, Siti; Putri, Ninda Oktaviani; Erinaldi, Erinaldi (CV. Civiliza Publishing, 2025)
This study analyzes the implementation of the Waste Bank Management Information System (Sistem Informasi Manajemen Bank Sampah/SIMBA) and its role in enhancing community participation in environmental management in Dumai City, Indonesia. Waste management has become a pressing issue in urban areas, and Dumai faces significant challenges due to limited infrastructure and low public awareness. SIMBA, a web-based platform developed by the Ministry of Environment and Forestry, integrates national waste bank data to support efficient, transparent, and measurable waste management. Using a literature review approach, this study compiles and synthesizes findings from relevant national and international research related to management information systems and public participation in environmental governance. The findings indicate that SIMBA has improved data transparency, administrative efficiency, and citizen engagement by enabling residents to monitor waste deposits and economic returns in real time. The system motivates behavioral change by linking ecological awareness with tangible financial benefits. However, implementation barriers persist, including limited technological infrastructure, low digital literacy among waste bank managers and users, and insufficient local policy and funding support. To overcome these challenges, the study recommends capacity building through digital literacy training, stronger collaboration between government, community, and private sectors, and policy optimization using data-driven decision-making. Overall, SIMBA demonstrates strong potential as a strategic instrument for promoting participatory, adaptive, and sustainable environmental management at the local level.